Pengembangan Kurikulum PAI Di SMP N 22 Rejang Lebong Untuk Membentuk Generasi Qurani - Ferti silviana lianvani; Maria Botifar; Deriwanto Deriwanto (Jurnal Literasiologi, 2023)
To form a Qur'anic generation, it must be well managed and sustainable through formal and non-formal education. The Qur'anic generation does not just appear but through habituation and education in the family, namely instilling religious education according to the level of development, instilling love and affection in the family and surrounding environment, intensive monitoring of activities carried out by children so that they do not fall into disobedience. The ability to read the Qur'an is the proficiency or ability to recognize hijaiyah letters and be able to read them in a series of verses of the Qur'an in a tartil manner. The ability to read the Qur'an of students in this case includes indicators of the fluency of students' reading in reciting the recitation of the Qur'an. In addition, the indicator that must be achieved is the ability of students to recite readings that are in accordance with the correct tajwid and makhraj.